Patients with Terminal Interstitial Pneumonia Require Comparable or More Palliative Pharmacotherapy for Refractory Dyspnea than Patients with Terminal Lung Cancer - Hiroko Okabayashi; Hideya Kitamura; Satoshi Ikeda; Akimasa Sekine; Tsuneyuki Oda; Tomohisa Baba; Eri Hagiwara; Takuro Sakagami; Takashi Ogura (Palliative Medicine Reports, 2021)
Background: Dyspnea is a severe symptom of terminal-stage interstitial pneumonia (IP). We commonly use continuous morphine or midazolam for terminal refractory dyspnea. Objective: We aimed to determine whether there is a difference in the use of continuous morphine and midazolam for terminal dyspnea between IP patients and lung cancer (LC) patients. Design: This is a single-center retrospective study. Setting/Subjects/Measurements: We retrospectively examined the clinical records of IP and LC patients who had died in our hospital. These patients were divided into the IP and LC groups to compare the use of morphine and midazolam. Results: Continuous morphine was administered to 50.0% of those in the IP group and 38.0% of those in the LC group for terminal dyspnea. There was no difference in the effect at six hours after morphine initiation between the two groups, but the concomitant use of continuous midazolam and morphine was more common in the IP group than in the LC group. The dose of continuous midazolam was significantly higher in the IP group than in the LC group, and the survival time after morphine initiation was significantly shorter in the IP group. Conclusions: The efficacy of continuous morphine administration for terminal dyspnea in IP patients was similar to that in LC patients for a short time after initiation, but just before death, more patients in the IP group required concomitant use of midazolam and morphine. Thus, IP patients require comparable or more palliative treatment than LC patients.